2010
DOI: 10.1111/j.1471-4159.2010.06807.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of acetyl‐l‐carnitine for energy and neurotransmitter synthesis in the immature rat brain

Abstract: Acetyl-L-carnitine (ALCAR) is an endogenous metabolic intermediate that facilitates the influx and efflux of acetyl groups across the mitochondrial inner membrane. Exogenously administered ALCAR has been used as a nutritional supplement and also as an experimental drug with reported neuroprotective properties and effects on brain metabolism. The aim of this study was to determine oxidative metabolism of ALCAR in the immature rat forebrain. Metabolism was studied in 21 day old rat brain at 15, 60 and 120 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 69 publications
5
85
0
1
Order By: Relevance
“…This mechanism of action might be particularly important during reperfusion after cerebral ischemia, when the mitochondrial redox state is hyperoxidized, ROS production is elevated, and there are increased markers of oxidative molecular modification (Perez-Pinzon et al, 1999;Fiskum et al, 2004). There is evidence for mitochondrial metabolism of both ketone bodies, e.g., b-hydroxybutyrate, and acetyl-L-carnitine after acute brain injury, which is associated with a reduction in oxidative stress and neuroprotection (Rosenthal et al, 1992;Liu et al, 1993;Prins et al, 2005;Scafidi et al, 2010Scafidi et al, , 2011. While there is less evidence that neuroprotection by exogenous pyruvate is a consequence of its oxidative metabolism, support for this mechanism comes from recent measurements of brain slice O 2 consumption indicating that exogenous pyruvate significantly elevates endogenous respiration (Schuh et al, 2011).…”
Section: Protection Against Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…This mechanism of action might be particularly important during reperfusion after cerebral ischemia, when the mitochondrial redox state is hyperoxidized, ROS production is elevated, and there are increased markers of oxidative molecular modification (Perez-Pinzon et al, 1999;Fiskum et al, 2004). There is evidence for mitochondrial metabolism of both ketone bodies, e.g., b-hydroxybutyrate, and acetyl-L-carnitine after acute brain injury, which is associated with a reduction in oxidative stress and neuroprotection (Rosenthal et al, 1992;Liu et al, 1993;Prins et al, 2005;Scafidi et al, 2010Scafidi et al, , 2011. While there is less evidence that neuroprotection by exogenous pyruvate is a consequence of its oxidative metabolism, support for this mechanism comes from recent measurements of brain slice O 2 consumption indicating that exogenous pyruvate significantly elevates endogenous respiration (Schuh et al, 2011).…”
Section: Protection Against Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…In addition to carnitine, acetyl-L-carnitine, which is another endogenous OCTN2 substrate, is also known to be a physiologically multi-talented molecule, not simply an energy source. It can be used for amino acid synthesis, 46) and acts as a nutraceutical with anti-oxidative effects. 47,48) Consistently, acetyl-L-carnitine is expected to ameliorate several brain disease conditions, such as depression 49) and ischemia.…”
Section: Other Organic Cation Transportersmentioning
confidence: 99%
“…There are no published studies, however, that have tested neuroprotection by ALCAR in the injured immature brain, where the pathophysiology is significantly different from that of the mature brain [2,35,36,37]. We have recently demonstrated that following systemic administration, the acetyl moiety of 13 C-labeled ALCAR is metabolized for energy via the TCA cycle in astrocytes and neurons within the forebrains of 21- to 22-day-old rats [38]. Furthermore, 13 C from ALCAR was incorporated into γ-aminobutyric acid (GABA), glutamate and glutamine, which are formed subsequent to TCA cycle metabolism [38].…”
Section: Introductionmentioning
confidence: 99%